Social and demographical determinants of quality of life in people who live with HIV/AIDS infection: evidence from a meta-analysis. (2nd January 2020) - Ghiasvand, Hesam; Higgs, Peter; Noroozi, Mehdi; Ghaedamini Harouni, Gholamreza; Hemmat, Morteza; Ahounbar, Elahe; Haroni, Javad; Naghdi, Seyran; Nazeri Astaneh, Ali; Armoon, Bahram
ABSTRACT: The aim of this meta-analysis is to summarize the available evidence on the social and demographic determinants of health-related quality of life (QoL) for HIV-infected populations in order to provide a direction to policy makers, planners, and program developers on how best to use their resources to improve the QoL of HIV-infected people. PubMed, Science Direct, Web of Science, and Cochrane electronic databases were searched (up to February 2017) to identify the relevant studies. A meta-analysis was conducted with procreate polled odds ratios (ORs and β) and the confidence intervals of 95% on determining factors of QoL in social and demographic terms. Random effect model was applied to calculate pooled estimation, due to varied sampling methods of researches. In total, 5607 papers were identified from 4 databases and additional search in reference lists. Of these, 2107 articles were selected for full-text review. We included 19 studies that met the eligibility criteria. The pooled effect size shows a relative positive impact of social support for QoL among HIV/AIDS patients and its lower boundary is about 0.61 and the higher about 1.49. The pooled effect size has a considerable negative impact stigma on people who live with HIV/AIDS (PWLHs') QoL ranges from −0.34 to −0.32. Low socioeconomic status (poverty situation) was found to have a degenerative impact with PWLHs' QoL. Our finding indicates an association between younger 35 and QoL is negative with a relatively wide range, the minimum level of education has a weak association with PWLHs' QoL (ES: 0.14–0.2). There are several sociodemographic determinants of QoL among PWLHs and in this study, we found that stigma, low level of socioeconomic status, and being younger than 35 years old have a negative association with QoL, while the social support showed a positive association and a minimum level of education did not show a rigorous negative or positive association.